Pregnancy after kidney transplantation: an observational study on maternal, graft and offspring outcomes in view of current literature - Stavart, Louis; Verly, Camille; Venetz, Jean-Pierre; Baud, David; Legardeur, Helene; Vial, Yvan; Golshayan, Dela (Frontiers in Nephrology, 2023)
Introduction Pregnancy after kidney transplantation (KTx) is considered to have a high risk of non-negligible complications for the mother, the allograft, and the offspring. With an increased incidence of these pregnancies over the past decades, transplant nephrologists and specialized obstetricians face increasing challenges, with scarce literature regarding long-term outcomes. Methods We retrospectively collected data from all women with at least one live birth pregnancy after KTx who were followed at our tertiary hospital between 2000 and 2021 to study maternal, graft and fetal outcomes. Results Ten patients underwent 14 live birth pregnancies after KTx. Preponderant maternal complications were stage 1 acute kidney injury (43%), urinary tract infections (UTI, 43%), progression of proteinuria without diagnostic criteria for preeclampsia (29%), and preeclampsia (14%). Median baseline serum creatinine at conception was 126.5 µmol/L [median estimated glomerular filtration rate (eGFR) 49 mL/min/1.73m2], and eGFR tended to be lower than baseline at follow-ups. Overall, there was no increase in preexisting or occurrence of de novo donor-specific antibodies. No graft loss was documented within the 2-year follow-up. There were nine premature births (64%), with a median gestational age of 35.7 weeks. The median birth weight, height, and head circumference were 2,560 g, 45.5 cm, and 32.1 cm, respectively. These measurements tended to improve over time, reaching a higher percentile than at birth, especially in terms of height, but on average remained under the 50th percentile curve. Discussion Overall, pregnancies after KTx came with a range of risks for the mother, with a high prevalence of cesarean sections, emergency deliveries, UTI, and preeclampsia, and for the child, with a high proportion of prematurity, lower measurements at birth, and a tendency to stay under the 50th percentile in growth charts. The short- and long-term impact on the allograft seemed reassuring; however, there was a trend toward lower eGFR after pregnancy. With these data, we emphasize the need for a careful examination of individual risks via specialized pre-conception consultations and regular monitoring by a transplant nephrologist and a specialist in maternal–fetal medicine during pregnancy. More data about the long-term development of children are required to fully apprehend the impact of KTx on offspring.